(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2021)
A composite material is a material that consists of a matrix (base phase) and a stiffener (reinforcement) that combined together to build up a structural unit. Reinforcement material form may be fibers, flakes or as a particle. In the current paper, unsaturated polyester resin (UP) was used as a base material, Sisal fibers (SF), glass fibers (GF) and Silica dioxide (SiO2) particles were performed as a reinforcing material. Three composite types were prepared: (C1) UP only, (C2) UP reinforced with 15% SF and 15% GF, and (C3) UP reinforced with 15% SF and 15% SiO2 to investigate the effect of reinforcement type on some mechanical properties such as elastic modulus, compressive strength, hardness and impact toughness with various temperatures. The experimental results showed that the mechanical properties of composite materials were improved by using reinforcement with fibers and nanoparticles. The high values of elasticity, hardness and toughness were obtained with the specimen C2 composite. While the highest values of compressive strength were obtained with the specimen C3. On the other hand, the modulus of elasticity, compressive strength and hardness were decreased with increasing of temperature values with various percentages. Other clockwise, the toughness values were increased